The European Research Framework Programme and innovation performance of companies. An empirical impact assessment using a CDM model - Abraham Garcia (European Commission, Joint Research Centre (JRC), 2011)
The effect of the EU Research Framework Programme (FP) on European company innovation performance is analysed for the period 1998-2000. The possibility of applying for the grant might make companies engage in new projects which they would not have considered if the fund was not there. In addition, the FP programme increases collaboration with other innovation agents (e.g., universities, research labs, governments and other firms). Both the existence of FP and collaboration are simultaneously modelled when innovation performance is studied. To measure innovation performance, an input indicator (level of R&D expenditure) is used in combination with an output indicator (increase in the innovation sales). Following Crepon et al. (1998) a simultaneous equations system is used with four equations (FP, collaboration, R&D and Innovation sales). The paper finds a positive impact for the FP on collaboration, and both factors positively affect the innovation performance (R&D and Innovation sales) of European firms. No crowding-out effect is found in the analysis.
Keywords: 330; Funding; Framework Programme; R&D investment; CIS; CDM model